Development of passive system for high temperature wireless sensor applications - Sarraf, Mohammad Javadian (2012)
Since the first work on surface acoustic wave (SAW) devices was presented in 1970,various aspects of research on these devices started to emerge due to their advantages such as small in size, low power consumption, low sensitivity to electromagnetic noises and wide range of operational temperature. Being passive and having these benefits introduce SAW-devices as the best candidate for constructing a passive wireless sensor system based on them. Operation of this system at harsh environment can be guaranteed by proper selection of materials that are used in SAW-devices fabrication. In order to reduce power consumption the size of devices in these systems should be as small as possible. Better impedance matching can guarantee better sensitivity and higher readout distance for sensor system. Parasitic elements due to wire bonding second level interconnection can degrade the impedance matching. In this thesis, a pure planar second level interconnection method using Double SAW Resonator System (DSAWRS) for passive wireless system is proposed to reduce parasitic effects of wire bonding interconnection. DSAWRS consists of two SAW resonators and a matching circuit for each resonator. A sensor element is added to the circuit as a capacitive or inductive element. The resonator and the sensor element in this system are separated for optimization. To reduce the size of devices, a single port SAW-resonator with the center frequency of 433.92 MHz has been developed to operate at 400 C on a new piezoelectric substrate (which is Gallium Orthophosphate (GaPO4)). The resonator has been designed based on GaPO4 with 5 Y-Boule cut with synchronous interdigital transducer (IDT) made from platinum and chromium as adhesion layer. The resonator consists of 50 fingers IDT and two 100 shorted strips reflector, with finger width of 1.3μm. The common method for matching the resonators is using their equivalent circuits. This method is not applicable for the high temperature. Different types of matching circuits have been studied and a new method for performing the matching process is proposed for the high temperature resonators. Here, a meander line inductor and interdigital capacitors have been used for implementing inductors and capacitors of the matching circuit. The characteristics of meander line inductors and interdigital capacitors have been studied and a design method is proposed for each one. DSAWRS employs second level interconnection for the high temperature (400 C) on alumina with platinum and silver as metal traces using thick film technology. Coplanar waveguide has been used as the transmission line and integrated to DSAWRS on the alumina. As a conclusion, a new method for design and fabricating the DSAWRS has been proposed and successfully applied on the profile of the second order interconnection that can operate up to 400 C.